Digital diplomatic crisis communication: diplomatic signalling and crisis narratives in an age of real – time governance - Cassidy, J (2017)
The practice of digital diplomatic signalling (DDS) and online crisis narratives (OCN) offers unexplored potential for analysing the creation and exercise of diplomatic communicative strategies during times of political crisis. Set within the global information space, the processes of DDS and OCN today carry the potential, to act as communicative tools for foreign policy power projection, and virtual powers of enlargement as the ‘battle for crisis narratives’ is now played out online. By developing a unique conceptual lens in which to view and analyse these communicative processes online, this research argues that digital signalling and online crisis narratives have become essential components of a Ministries of Foreign Affairs (MFAs) communicative toolbox, and worthy instruments in which they can seek to exert and extend their diplomatic influence both at home and abroad. Using DDS and OCN as conceptual lenses in which to view diplomatic crisis communication practices, we see that the power inherent in digital mediums becomes a communicative advantage during a crisis and a strategic instrument for the achievement of foreign policy goals. A new crop of studies which addresses the emergence of communicative power under the label ‘foreign policy in global information space’ adds substantial weight to these claims, supplying, new ways of extrapolating the power projections of digital diplomatic actors online. Through the exploration of two distinct case studies, the 2014 Israel-Gaza conflict, and 2013/4 Euromaidan crisis, this research therefore taps into the unexplored potential of the process of DDS, its power to create OCN’s, and ultimately expand a state's power and influence during times of crisis.